If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 75x + 38y = 1000 Solving 75x + 38y = 1000 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-38y' to each side of the equation. 75x + 38y + -38y = 1000 + -38y Combine like terms: 38y + -38y = 0 75x + 0 = 1000 + -38y 75x = 1000 + -38y Divide each side by '75'. x = 13.33333333 + -0.5066666667y Simplifying x = 13.33333333 + -0.5066666667y
| (10b+7)(3b-9)=0 | | 0=16t^2+64t-28 | | 8-h/5=11 | | 40=-16t^2+96t+12 | | 30+7x=9 | | 3y-48= | | 5(X+3)=2x+7 | | x^3-4x^2+2.5=0 | | (X+2)(Y-1)=(X+7)(Y-3) | | 9x-35-9x=14x-9x | | 4x+3x^2=248 | | 12x^3-48x^2+30=0 | | 7(2p+3)+6(p-2)=10p+29 | | n^3-3n^2-10=0 | | 15w-12/w=11 | | ln(x)+x-2=0 | | 15h=24+11h | | 5X^2+4x-288=0 | | 28s+49s^2t= | | 10y+23=4y+13 | | 19x-12=24 | | 12-6x=84 | | 2x+3x-1=68 | | 2w^4-13w^2+15=0 | | 4*x^4-9*x^2+2x+3=0 | | -20=17x-38 | | 10(r-3)=40 | | (x^2-100)(x^2-10)=0 | | 2x+3-x=43+6x | | 6x-1=2(3x+2) | | 6x-1=3(3x+2) | | 100x^2-4y^2= |